(3TQM GdSde GdefhQb (B" (3GdeQhfb (B"s - (3YHO GdQMef Hf eMeO GdUZjQ GdGNVQj, CHh RjO,J (B983 (3g` s ((3eMeO Hf eMdGS s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd bdhH GdYdeGA SeGhGJ JJLdi HgG TehS GdeYGQa CeG HYO adeG hVYJ GdCQLhRI GdeSeGI H(B" (3GdSd(B" (3GdefhQb ai Yde GdefWb RGhOfi HYV GdENhGf GdeQI HYO GdeQI Ydi Cf CVY YdjgG TQMkG eajOkG s
(3BNQgG (B:s
(3hdaX GdCHQL LeY bdI , hGdMQGA GdcKjQ , dCfgG EKfG YTQ HQLkG hjchf Whd Gdedhjf hbUQgeG HMSH Gddjd GdTeGdi hUdi Gddg Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdfXe ajgG HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B331s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B998s
Keywords: (3GdadSaI hGdefWbs